NEGOTIATING ISLAMIC BROADCASTING ETHICS: EXAMINING DIGITAL DA'WAH TRENDS AND THEOLOGICAL INTEGRITY ON TIKTOK AND INSTAGRAM REELS - Muhammad Riduan; Mohammad Rofiq; Ahmad Zinuddin (Bayan lin-Naas : Jurnal Dakwah Islam, 2026)
Abstract The rapid digitalization of Islamic Broadcasting and Communication (KPI) has birthed the "Dakwah Santuy" (casual preaching) trend on social media, specifically targeting Generation Z. However, this trend faces the stigma of theological dilution due to the algorithmic pressures of short-form video platforms that prioritize engagement over depth. This study aims to analyze the strategies used by content creators to package da'wah messages effectively while preserving theological substance. Utilizing a qualitative netnography approach, data were gathered through non-participant observation on TikTok and Instagram Reels, alongside in-depth interviews with three prominent da'wah creators. The findings reveal that creators navigate algorithmic constraints through two primary strategies: first, semantic shifts involving "The 3-Second Hook" that adapt rigid classical terminology into relatable everyday pragmatics; second, "pedagogical compensation," where short videos act purely as emotional triggers while complex theological evidence (dalil) and jurisprudence (fiqh) are relegated to captions or pinned comments. This dual-format approach successfully bridges classical Islamic literature with modern digital literacy. The study concludes that digital da'wah can maintain its hermeneutic integrity and ethical boundaries by strategically adapting linguistics and utilizing platform features comprehensively.